Improving the Mechanism of Working with Low-Achieving Students on the Basis of Texts and Assignments Studied in International Assessment Programs (Eurasian Journal of Learning and Academic Teaching, 2022)
Today, the understanding of the assessment system is further complicated by the trends that are observed in this area - this is the ever-increasing internationalization of debate, the growing importance of questions about the transnationalization of education, where the question of “using” the best practices in curriculum development and the adoption of foreign systems arises; opening up more opportunities for international student mobility, as well as employment opportunities in foreign countries for graduates (where there is a need for international recognition of qualifications).